Hepatitis C virus hypervariable region 1 antibodies interrupt E2-SR-B1 interaction to suppress viral infection - Kai Deng; Qing Zhou; Zhanxue Xu; Yuhao Yang; Xi Liu; Chunna Li; Mingxiao Chen; Zhenzhen Zhang; Haihang Chen; Ling Ma; Muhammad Ikram Anwar; Changlong Zheng; et al. (iScience, 2023)
Summary: Whether hypervariable region 1 (HVR1)-targeting antibodies elicited during natural hepatitis C virus (HCV) infection contribute to virus clearance and what is the mechanism underlying remain unclear. Here, we demonstrated that treatment of HCV-infected hepatoma Huh7.5 cells with the IgGs purified from 2 of 28 (7.1%) chronic hepatitis C (CHC) patients efficiently controlled the infection, for which genotype 1b HVR1 (1bHVR1)-binding antibody was critical. Moreover, we found that 1bHVR1 peptide was superior to 2aHVR1 in rabbit immunization to elicit antibodies neutralizing genotypes 1a, 2a, 3a, and 4a. The neutralization effect of 1bHVR1 IgG could be augmented by HH-1, an antibody constructed from CHC memory B cells but without binding to HVR1 peptide. Mechanistic studies showed that 1bHVR1 antisera and IgGs disrupted the interaction of E2-SR-B1 receptor. This study highlights the neutralizing activity of HVR1 antibody elicited by CHC patients and generated by HVR1-immunization against the established infections of multiple HCV genotypes.